2003
DOI: 10.1159/000068121
|View full text |Cite
|
Sign up to set email alerts
|

Transcription at Early Stages of Herpes Simplex Virus 1 Infection and during Reactivation

Abstract: Objective: The kinetics of immediate early (IE) and early (E) herpes simplex virus 1 (HSV-1) mRNA transcription was followed in explanted trigeminal ganglia from rabbits with established latency. Methods: The expression of IE and E mRNAs was first assessed in infected Vero cells by RT-PCR and then in explanted trigeminal ganglia by nested RT-PCR. Results: In infected Vero cells, IE mRNAs [for infected cell protein (ICP) 0, ICP4 and ICP27] were first detected 1–2 h post-inoculation (p.i.), peaking at 3 h p.i. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…It had been reported that viral DNA replication (36), production of infectious virus (37), and staining of multiple, adjacent cells with anti-HSV-1 sera (47) were not observed before 48 h p.e., sug- In addition to supporting our ISH results, the RT-PCR experiments provided quantitative information on RNA expression levels in individual TG. Whereas some studies have relied on pooling ganglia (24,28,43) and have rarely detected productive-cycle gene expression during latency (9,24,28,43), our sensitive assays have detected genes from all kinetic classes in individual TG in this study and others (2,3,18,19). Although the variability observed between individual TG can impede achievement of statistical significance for certain comparisons, it provides a clear picture of the natural variation among latent and reactivating ganglia.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It had been reported that viral DNA replication (36), production of infectious virus (37), and staining of multiple, adjacent cells with anti-HSV-1 sera (47) were not observed before 48 h p.e., sug- In addition to supporting our ISH results, the RT-PCR experiments provided quantitative information on RNA expression levels in individual TG. Whereas some studies have relied on pooling ganglia (24,28,43) and have rarely detected productive-cycle gene expression during latency (9,24,28,43), our sensitive assays have detected genes from all kinetic classes in individual TG in this study and others (2,3,18,19). Although the variability observed between individual TG can impede achievement of statistical significance for certain comparisons, it provides a clear picture of the natural variation among latent and reactivating ganglia.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, it has been reported that during explant reactivation from murine TG, E and leaky late transcripts are detected before IE transcripts (43). On the other hand, a recent investigation of this question with rabbit TG found no deviation from the canonical regulatory order (28).…”
mentioning
confidence: 82%
“…Several groups have studied HSV gene transcription and translation in explanted ganglia as a model of reactivation (4,6,10,18,24,25,33,34). In some cases it was concluded that the transcriptional program during reactivation differed from that seen during lytic infection or that viral DNA replication was required for immediate-early gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Since the gene encoding the ICP0 protein of HSV-1 is contained entirely within the region of the HSV-1 genome encoding LATs (reviewed in reference 3), it might be transcribed during latency, as recently reported by Chen et al for latently infected TG neurons (10). ICP0 is the first viral protein produced during the productive cycle and is thus classically considered a relevant indicator of early-stage reactivation (18,59,65). It nonspecifically transactivates both viral and cellular promoters (18,25,42) and plays a crucial role in the initiation of productive infection following low-multiplicity infections of cells in culture (7,8,17,63).…”
mentioning
confidence: 99%